School-Related and Individual Predictors of Subjective Well-Being and Academic Achievement - Steinmayr, Ricarda; Heyder, Anke; Naumburg, Christian; Michels, Josi; Wirthwein, Linda (Frontiers in Psychology, 2018)
Recent research in the educational context has focused not only on academic achievement but also on subjective well-being (SWB) as both play a major role in students’ lives. Whereas the determinants of academic achievement have been extensively investigated, little research has been conducted on school-related determinants of SWB in comparison with other students’ characteristics. In the present cross-sectional study, we set out to investigate whether perceived school climate predicts school grades and SWB above and beyond other variables that are important for SWB and academic achievement. A sample of 767 8th and 9th grade students (n = 361 female adolescents; age: M = 14.07 years, SD = 0.92) completed measures of SWB, perceived school climate, test anxiety, self-efficacy, and interest. Grade point average (GPA) indicated students’ academic achievement. Data were analyzed with latent structural equation models in which GPA and SWB were regressed on the school climate variables and students’ characteristics. Results indicated that a positive school climate as well as self-efficacy and the worry component of test anxiety predicted SWB and/or GPA after all other variables were controlled for. Directions for future research and the importance of school climate variables on adolescents’ SWB and academic achievement are discussed.